Seasonal and Spatial Variations of Meiofauna Communities in Correlation to Environmental Characteristics in the Organic Shrimp Farms of Tam Giang Commune, Nam Can District, Ca Mau Province - Tran, Thanh Thai (H. : ĐHQGHN, 2018)
p. 55-64